Quasi-Fiscal Operations of Public Financial Institutions - Mackenzie, George; Stella, Peter (Washington, D.C. : International Monetary Fund, 1996)
Central banks and other public financial institutions act as agents of fiscal policy in many countries. Their "quasi-fiscal" operations and activities can affect the overall public sector balance without affecting the budget deficit as conventionally measured, may also have important allocative effects, and increase the effective size of the public sector. This paper analyzes the macroeconomic and financial effects of such quasi-fiscal activities, as well as the taxes, subsidies, and other expenditures that such activities introduce outside the budget. Measurement and accounting issues are addressed, and policy recommendations are offered.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet